British folk tales - Crossley-Holland, Kevin (New York Orchard Books, 1987)
The rich body of British folklore, myth, and legend comes to life in a retelling of fifty traditional tales--including "Mossycoat," an English version of "Cinderella," and "The Sea Woman," about a young Scot's love for his selkie-wife
59803
Keywords: Tales -- Great Britain